2020
DOI: 10.14198/jhse.2021.163.14
|View full text |Cite
|
Sign up to set email alerts
|

How to develop professionally important soft-skills for IT-professionals by means of physical education?

Abstract: Information on features necessary for productive professional work is interesting for both scientists and employers. Single systematized contradictory data don't allow to improve training programs, make effective training programs for IT-specialists for productive professional work. Goal -identify critical important, important and desirable professional qualities for IT-specialists, according to the data of literature determine the most important means of their effective development. Methods, participants, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
3
0
3
Order By: Relevance
“…It was determined that concentration, stability, span and switching attention are related to agility (see Table 6). Our results coincide with our previous data on positive influence of agility development tools towards attention indicators in students of the Institute of Information Technologies (Andres, 2019(Andres, , 2021. Our data confirm the data of specialists (Pichurin, 2015), who proved the fact of improvement in selectivity, concentration and stability of attention with increasing of general level of physical fitness of students and, especially, coordination abilities.…”
Section: Figure 3 the Number Of Noticeable And Dense Correlation Coef...supporting
confidence: 92%
See 1 more Smart Citation
“…It was determined that concentration, stability, span and switching attention are related to agility (see Table 6). Our results coincide with our previous data on positive influence of agility development tools towards attention indicators in students of the Institute of Information Technologies (Andres, 2019(Andres, , 2021. Our data confirm the data of specialists (Pichurin, 2015), who proved the fact of improvement in selectivity, concentration and stability of attention with increasing of general level of physical fitness of students and, especially, coordination abilities.…”
Section: Figure 3 the Number Of Noticeable And Dense Correlation Coef...supporting
confidence: 92%
“…Analysis of special literature showed that psychophysical training contributes to solving the tasks of preparation for work. The expediency of increasing level of development of psychophysical preparation in studentsrepresentatives of relatively peaceful professions: IT specialists, railway workers, economists, designers (Andres, 2019;Andres, 2021;Chernovsky & Kolumbet, 2016;Kozina et al, 2014;Ostapenko, 2014;Pichurin, 2015) has been proven. At the same time, it has been proven that training programs, using agility development tools are particularly effective for the formation of a number of professionally important competencies (Kozina et al, 2014;Lisowski & Mihuta, 2013;Ostapenko, 2014;Pichurin, 2015;Rolyuk, 2015;Shalupin et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physical abilities can assist students in showing their quality skills [27]. If traditional games can be taught as a physical activity exercise in physical education [28], children will be able to develop good physical abilities that will help them improve in terms of cognitive, affective, and psychomotor development [29] Discipline, cooperation, responsibility, honesty, hard work, and educational values are all taught through traditional games [31]. Traditional games educate educational and moral values while also building a spirit of nationalism [33].…”
Section: материал и методыmentioning
confidence: 99%
“…Diversos estudos realizados por essas e outras referências, como apontado por Vial (2019), mostram que a tecnologia é apenas uma peça no meio de um emaranhado de fatores que provocam essa transformação em todos ambientes de convivência na sociedade. Por este motivo, emergem investigações sobre o efeito comportamental dos profissionais sobre esse fenômeno e sobre como essas características -também chamadas de soft skills (Andres, 2021) -são necessárias para a adaptação neste universo sob novas perspectivas.…”
Section: Introductionunclassified
“…Essas habilidades "soft" não são mais encaradas como diferenciais ou itens alheios à rotina de trabalho, mas "sim como uma parte significativa do papel do trabalho" (Sulea 2018, p. 56) devido à alta complexidade desse novo ambiente profissional que se desenha, permeado fortemente por demandas de relações interpessoais. Essa necessidade, segundo Sulea (2018) existe tanto para profissões mais estáveis diante a as previsões para o futuro do trabalho (como os profissionais de Tecnologia da Informação em geral) quanto àquelas consideradas redundantes, e definem fatores de competitividade a nível individual e organizacional (Andres, 2021;Sulea, 2018).…”
Section: Introductionunclassified